Risk of visual axis opacification in infants with and without primary IOL implantation after congenital cataract surgery performed during the first 4 months of age - Hložánek, Martin; Cilečková, Lenka; Alió, Jorge L; Autrata, Rudolf; Zelenayová, Nina; Komínek, Martin; Cendelín, Jiří; Mahelková, Gabriela (Graefe's archive for clinical and experimental ophthalmology, 2023)
PURPOSE: The study evaluates the rate of postoperative formation of a pupillary membrane (PM) and posterior visual axis opacification (PVAO) in infants with and without primary IOL implantation during the first 4 months of infancy. METHODS: Medical records for 144 eyes (101 infants) operated between 2005 and 2014 were evaluated. A posterior capsulectomy and anterior vitrectomy were performed. Primary IOL implantation was performed in 68 eyes, while 76 eyes were left aphakic. There were 16 bilateral cases in the pseudophakic group and 27 in the aphakic group. The follow-up period was 54.3 ± 21.05 months and 49.1 ± 18.60 months, respectively. Fisher's exact test was used for statistical analysis. The two-sample t-test with equal variance was used to compare surgery age, follow-up period and time intervals of complications. RESULTS: The mean age of surgery was 2.1 ± 0.85 months in the pseudophakic and 2.2 ± 1.01 months in the aphakic group. PM was diagnosed in 40% pseudophakic and 7% aphakic eyes. A second surgery for PVAO was performed in 72% pseudophakic and 16% aphakic eyes. Both were significantly higher in the pseudophakic group. In the pseudophakic group, the number of PVAO was significantly higher in infants operated before 8 weeks of age compared to surgery age 9-16 weeks. The frequency of PM was not age-dependent. CONCLUSION: Although it remains feasible to implant an IOL during the primary surgery, even in very young infants, there should always be solid arguments for this decision since it puts the child at higher risk of repeated surgeries under general anaesthesia.
Keywords: katarakta; Lenses, Intraocular; Infant; Humans; afakie; kojenec; extrakce katarakty; dítě; Aphakia; Child; lidé; Cataract; Postoperative Complications; Lens Implantation, Intraocular; pooperační komplikace; Follow-Up Studies; Cataract Extraction; Retrospective Studies; implantace nitrooční čočky; retrospektivní studie; Visual Acuity; nitrooční čočky; zraková ostrost; následné studie